Konsep Dasar Pendidikan: Menumbuhkan Pemahaman untuk Menciptakan Pembelajaran yang Berkualitas - Habsy, Bakhrudin All; Nurjanah, Intan; Putri, Shafyra Ayunda; Naisyla, Alinza Zahra (Lembaga Yasin AlSys, 2024)
Education is a process of humanization that plays a crucial role in shaping individuals into moral, critical, and beneficial members of society. This process aims not only to provide knowledge but also to develop skills and attitudes that support the progress of individuals and the nation. This research aims to explore and analyze the concept of educational science and its role in shaping individuals who are character-driven and competitive in society. This research uses qualitative research methods, with data collection techniques including literature study from journals, books, articles, and other scholarly works relevant to the subject of this study. The results of this research include (1) Definition of Education (2) Role of Educators (3) Role of Learners (4) Role of Educational Institutions (5) Curriculum Policies (6) Learning Theories (7) Learning Motivation (8) Formation of Moral and Cultural Values through Education (9) Personality Development (10) Education as a Learning Process (Bloom's Taxonomy) (11) Educational Goals (12) Learning Methods (13) Long Life Education.